2016
DOI: 10.1007/s40890-016-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Road Crossing Behavior Under Mixed Traffic Conditions: A Comparative Study of an Intersection Before and After Implementing Control Measures

Abstract: Traffic accidents involving pedestrians have become a major safety problem in most of the developing countries like India due to rapid urbanization, increase in vehicular growth and lack of adherence to traffic regulations by both drivers and pedestrians. The existing roads design does not provide adequate facilities for pedestrians and hence, there exists a constant conflict between the pedestrians and the vehicles in sharing the limited space available on a road. At intersections, pedestrian crossing behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…Similar studies in India studies were conducted by [50,[105][106][107][108][109] over crosswalk and mid-block crossings respectively, and gap acceptance behaviour was mainly measured under mixed traffic condition. The study by [105] observed the average accepted gaps to cross intersections were 4.75 s, 3.35 s and 3.50 s by elderly, middle-aged and young pedestrians; while in 2014 the same authors [106] used Artificial Neural Network (ANN) technique to predict gap acceptance behaviour under different mixed traffic conditions.…”
Section: Crosswalk and Crossing Facilitysupporting
confidence: 55%
See 3 more Smart Citations
“…Similar studies in India studies were conducted by [50,[105][106][107][108][109] over crosswalk and mid-block crossings respectively, and gap acceptance behaviour was mainly measured under mixed traffic condition. The study by [105] observed the average accepted gaps to cross intersections were 4.75 s, 3.35 s and 3.50 s by elderly, middle-aged and young pedestrians; while in 2014 the same authors [106] used Artificial Neural Network (ANN) technique to predict gap acceptance behaviour under different mixed traffic conditions.…”
Section: Crosswalk and Crossing Facilitysupporting
confidence: 55%
“…The study by [105] observed the average accepted gaps to cross intersections were 4.75 s, 3.35 s and 3.50 s by elderly, middle-aged and young pedestrians; while in 2014 the same authors [106] used Artificial Neural Network (ANN) technique to predict gap acceptance behaviour under different mixed traffic conditions. In another study, [108] observed that 45.1% of the pedestrians utilised crosswalks, while average waiting time was 24.7 s. The before-after study by [109] showed that 4.65s and 7.07s were the average waiting times, before and after the installation of a signal. The decrease in walking speed was mainly due to one stage crossing which was available after signal installation, and thus pedestrians moved at a slower speed due to enhanced safety.…”
Section: Crosswalk and Crossing Facilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Traffic accidents involving pedestrians have become a major problem, especially in developing countries [1,2]. According to a WHO's Global status report on road safety, more than 1.2 million people die each year as a result of road traffic crashes and pedestrians make up 22% of these fatalities [3].…”
Section: Introductionmentioning
confidence: 99%